L‐Theanine Goes Greener: A Highly Efficient Bioprocess Catalyzed by the Immobilized γ‐Glutamyl Transferase from Bacillus subtilis. Issue 8 (13th March 2023) - Robescu, Marina S.; Alcántara, Andrés R.; Calvio, Cinzia; Morelli, Carlo F.; Speranza, Giovanna; Ubiali, Daniela; Bavaro, Teodora
Abstract: l ‐Theanine (l ‐Th) was synthesized by simply mixing the reactants (l ‐glutamine and ethylamine in water) at 25 °C and Bacillus subtilis γ‐glutamyl transferase ( Bs GGT) covalently immobilized on glyoxyl‐agarose according to a methodology previously reported by our research group; neither buffers, nor other additives were needed. Ratio of l ‐glutamine (donor) to ethylamine (acceptor), pH, enzymatic units (IU), and reaction time were optimized (molar ratio of donor/acceptor=1 : 8, pH 11.6, 1 IU mL −1, 6 h), furnishing l ‐Th in 93 % isolated yield (485 mg, 32.3 g L −1 ) and high purity (99 %), after a simple filtration of the immobilized biocatalyst, distillation of the volatiles (unreacted ethylamine) and direct lyophilization. Immobilized Bs GGT was re‐used (four reaction cycles) with 100 % activity retention. This enzymatic synthesis represents a straightforward, fast, high‐yielding, and easily scalable approach to l ‐Th preparation, besides having a favorable green chemistry metrics. Abstract : Making green t(h)ea greener : The sustainable synthesis of l ‐theanine is achieved by simply mixing l ‐glutamine and ethylamine in water with the immobilized γ‐glutamyl transferase from Bacillus subtilis, and stirring for 6 h. The product is obtained with a yield of 93 % and purity of 99 %. The biocatalyst can be recovered and reused for the next run.